Biomedical Profile of Hemoglobin Level, Nutritional Status, and Blood Type in Community-Based Health Screening at Pematang Kamasan Posyandu - Firda Asma’ul Husna; Ghea Farmaning Thias Putri; Dwi Widyawati; Rifdah Hanifah (International Journal of Cell and Biomedical Science, 2026)
Background: Community-based health screening is essential for the early detection of hematological abnormalities, nutritional disorders, and limited health awareness, particularly in rural populations with restricted access to routine medical services. Objective: This study aimed to describe hemoglobin levels, body mass index (BMI) status, blood type distribution, and community health knowledge among residents participating in Posyandu-based screening in Pematang, Kamasan Village. Methods: A descriptive observational study was conducted using secondary data from community health screening. Among 143 attendees, complete biomedical and knowledge assessment data were available for 45 participants. Variables included sex, hemoglobin level, BMI category, blood type, and awareness of personal blood type and hemoglobin status. Data were analyzed descriptively using frequency distribution, percentage, and mean ± standard deviation. Results: Female participants predominated in the screened population. Blood group O was the most common type, and obesity represented the dominant BMI category. Mean hemoglobin levels in both males and females were generally within normal physiological ranges. Despite measurable biomedical parameters, most participants were unaware of their personal blood type and hemoglobin status, indicating low community health literacy. Conclusion: This study demonstrates a coexistence of relatively normal hemoglobin status with high obesity prevalence and limited biomedical awareness in a rural community. Strengthening integrated community screening combined with targeted health education is necessary to improve preventive health behavior and reduce future cardiometabolic risk.